2000
DOI: 10.1603/0022-0493-93.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Cereal Aphids on Russian Wheat Aphid (Homoptera: Aphididae) Susceptible and Resistant Wheats

Abstract: Field experiments were conducted in 1997 and 1998 to evaluate the impact of resistance to Russian wheat aphid, Diuraphis noxia (Mordvilko), on the cereal aphid complex in wheat. Two spring wheats were planted: the variety "Centennial" (Russian wheat aphid susceptible) and the advanced line IDO488 (Russian wheat aphid resistant). IDO488 incorporates the resistance found in PI 294994 into a Centennial background. Field plots were artificially infested with adult D. noxia and sampled weekly. The most abundant aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Neither of the two D. noxia-resistant wheat accessions (Turtsikum and Strelinskaja Mestnaja) limited R. padi populations relative to control accessions. Similarly, Schotzko & Bosque-Pérez (2000) found no difference in field-population levels of R. padi between Centennial wheat and an advanced wheat line derived from the cross: Centennial/Strelinskaja Mestnaja.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neither of the two D. noxia-resistant wheat accessions (Turtsikum and Strelinskaja Mestnaja) limited R. padi populations relative to control accessions. Similarly, Schotzko & Bosque-Pérez (2000) found no difference in field-population levels of R. padi between Centennial wheat and an advanced wheat line derived from the cross: Centennial/Strelinskaja Mestnaja.…”
Section: Discussionmentioning
confidence: 90%
“…It is not known whether the same or different gene(s) are responsible for resistance to R. padi and D. noxia in N1185, N1186, Okto Derzhavina, and Stniism 3. Use of accessions with resistance to both R. padi and D. noxia would seem advantageous, as these aphids can co-occur at relatively high levels in several regions (Hammon et al, 1996;Schotzko & Bosque-Pérez, 2000). The strong levels of resistance in triticale accessions we tested warrant further research to determine the genetic basis of their resistance to R. padi and to clarify their potential use in breeding programs for cereal-aphid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Host plant resistance against insects is recognized as an important component of integrated insect pest management (Gao 1994;Schotzko and Bosque-pérez 2000;Li et al 2001). Plant resistance is attributed largely to secondary metabolites such as phenolics, nonprotein amino acids, and alkaloids, which are documented to be deleterious to insect herbivores (Manuwoto and Scriber 1985;Ciepiela and Sempruch 1999;Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These are the greenbug, Schizaphis graminum, the Russian wheat aphid, Diuraphis noxia, and the bird cherry-oat aphid, Rhopalosiphum padi (Homoptera: Aphididae) (Turney & Hoelscher, 1986; Schotzko & Bosque-Perez, 2000; Bosque-Pérez et al ., 2002). It has been shown that S.…”
Section: Introductionmentioning
confidence: 99%